Só nossa luta mesmo! Sociedade e reivindicações no bairro Morada do Sol e Indaiatuba–SP, 1980-2010 - Alves, Walter de Assis (2019)
The focus of this research is the analysis of interrelationships and social positioning experienced by men and women who are citizens of the city of Indaiatuba located in the metropolitan region of Campinas, in the interior of the state of São Paulo. The issue input the structural economics, political and social transformations designed in the middle of the process of the city’s growth, a dynamic that was stimulated from the mid-1970s through development policies planned at the state level, with the guiding purpose of the metropolitan restructuring in the city of São Paulo. The scenario enhaced the creation of municipal development plans in Indaiatuba, allowing the intensification of its industrialization process, just as the opening of popular allotments meant to accommodate the agglomeration of families in their search of work, such as Jardim Morada do Sol in the earlier 1980s. It is also in this scenario that groups’ practices who are part of the population in the city were reworked, a circumstance that demanded a critical reading of its unfolding, grounded on the sppining in the modes of daily living created by the expansion of its demography . The historical process in Indaiatuba during the decades after the population boost, it will be composed by the conjugation of established relationships in the chain of certain tensions among social spheres formed by old and new citizens, it is from the gathering between various realities that the city will move structured in spaces capable of accrediting new rhythms and meanings to urbanity, thus their neighborhoods, squares, churches and streets will experience a larger flow of people circulation, turning into places of approach and interaction, as well as confrontations and divergent relations between subjects with journeys and the most diverse experiences.